HUBUNGAN MAKNA: SUATU KAJIAN SEMANTIK - ., Nuryadi (Fakultas Komunikasi, Sastra, dan Bahasa, 2011)
This paper discusses and explains sense relation. We give different definition between sense and meaning. Sense is a meaning of lexical unit distinguished from other meaning. Meanwhile, meaning is traditionally of something said to be expressed by a sentence. The formal approach to capture the lexical knowledge in a format compatible with the model-theoretical approach is meaning postulates. It would recognize automatically from knowledge rather than state in terms of component meaning of either word. Speaker and hearer have knowledge about many kinds of sense relation. Sense relation is a meaning of a lexical unit within the semantic system of a language. Sense relations discussed in this paper are entailment, inclusion, contradiction, anomaly, ambiguity, polisemy, homonymy, meronymy, referensy, presupposition and synonymy. Besides, we discusses meaning of paraphrase, denotation and connotation